2017
DOI: 10.1126/sciadv.aao2538
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-like behavior of UV-irradiated interstellar ice analog at low temperatures

Abstract: UV-irradiated interstellar ice analog behaves like a liquid at 50 to 150 kelvin, below its crystallization temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 32 publications
4
30
0
Order By: Relevance
“…It should be noted that Eq. (15) agrees well with the diffusivity at T ≃ 60 K obtained by 28 , who demonstrated that liquid-like water forms from the UV-irradiated vapor-deposited amorphous ice around 50-140 K. The other thermal quantities of water adopted in this study are shown in Table 2.…”
Section: Basic Equationssupporting
confidence: 87%
See 1 more Smart Citation
“…It should be noted that Eq. (15) agrees well with the diffusivity at T ≃ 60 K obtained by 28 , who demonstrated that liquid-like water forms from the UV-irradiated vapor-deposited amorphous ice around 50-140 K. The other thermal quantities of water adopted in this study are shown in Table 2.…”
Section: Basic Equationssupporting
confidence: 87%
“…Additional future experiments for nanometer-sized droplets will provide constraints for thermodynamic quantities and improve the (15) 27as functions of temperature. The diffusivity at T = 60 K obtained by 28 with the use of D = kT /(6πηr o ) with viscosity η, is also shown.…”
Section: Basic Equationsmentioning
confidence: 97%
“…A presumable role of CO in the formation of nucleobases or their precursors might explain the failure to detect any nucleobases in the previous study 27 (see Supplementary Note 2 for further discussion). In addition, UV-exposed interstellar ice analogues are assumed to possess lower viscosity than amorphous solid water at temperatures above 65 K 28 , a feature that could potentially cause different chemical reactivity patterns at different temperatures. Sugars and their related molecules were abundant (more than several hundreds of ppm) 12 in organic residues that were produced via photolysis of interstellar ice analogues (H 2 O:CH 3 OH:NH 3 = 10:3.5:1) at 78 K, and were analysed using two-dimensional gas chromatography time-of-flight mass spectrometry.…”
Section: Discussionmentioning
confidence: 99%
“…interstellar/cometary ice analogues at temperatures < 80K exposed to UV photons/energetic particles 12,53,54 . Interestingly, Tachibana et al 55 showed that UV-irradiated interstellar ice analogues composed of water, methanol and ammonia, as well as of pure water show liquid-like behavior over 65-150 and 50-140 K temperature ranges, respectively, which may enhance the formation of complex organic species. Such ices, which are supposed to contribute to the organic inventory of meteorites, micrometeorites and interplanetary dust particles, could have served as a key source of biomolecular precursors for the prebiotic chemical origins of life 56,57 .…”
Section: Introductionmentioning
confidence: 99%